Splendid speller - O'Connor, Jane (O'Connor, Jane. Fancy Nancy., 2011)
Nancy, who loves to use fancy words, and her friend Bree are proud to be the best spellers in their class, but when a spelling quiz proves tougher than Nancy thought, Nancy is faced with a difficult decision.